2016
DOI: 10.1101/gr.209106.116
|View full text |Cite
|
Sign up to set email alerts
|

Global genome nucleotide excision repair is organized into domains that promote efficient DNA repair in chromatin

Abstract: The rates at which lesions are removed by DNA repair can vary widely throughout the genome, with important implications for genomic stability. To study this, we measured the distribution of nucleotide excision repair (NER) rates for UV-induced lesions throughout the budding yeast genome. By plotting these repair rates in relation to genes and their associated flanking sequences, we reveal that, in normal cells, genomic repair rates display a distinctive pattern, suggesting that DNA repair is highly organized w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 51 publications
9
55
0
Order By: Relevance
“…This enabled us to accurately map the nucleosome structure at positions of GG-NER complex binding in a similar fashion to that shown in Figure 2A. In agreement with our previously published Abf1 ChIP-chip data (Yu et al 2016), we found ~4,000 Abf1 binding sites detected by MACS2 (data not shown). It is well established that Abf1 exists in the cell in large excess over the other GG-NER components (Rad7 and Rad16), and has a wide range of different functions outside of GG-NER (Yarragudi et al 2007;Schlecht et al 2008;Ganapathi et al 2011;Zhang et al 2012).…”
Section: Identifying the Chromatin Context For The Linear Remodellingsupporting
confidence: 89%
See 4 more Smart Citations
“…This enabled us to accurately map the nucleosome structure at positions of GG-NER complex binding in a similar fashion to that shown in Figure 2A. In agreement with our previously published Abf1 ChIP-chip data (Yu et al 2016), we found ~4,000 Abf1 binding sites detected by MACS2 (data not shown). It is well established that Abf1 exists in the cell in large excess over the other GG-NER components (Rad7 and Rad16), and has a wide range of different functions outside of GG-NER (Yarragudi et al 2007;Schlecht et al 2008;Ganapathi et al 2011;Zhang et al 2012).…”
Section: Identifying the Chromatin Context For The Linear Remodellingsupporting
confidence: 89%
“…The Venn-diagram in Figure 3A enables us to identify various subcategories of Abf1 binding sites. We then used our previously published Rad16 ChIP-chip genome-wide occupancy data (Yu et al 2016) to refine this list by identifying the genomic positions enriched for GG-NER complex binding. This yielded 3,600 Abf1 binding sites that are enriched for Rad16.…”
Section: Identifying the Chromatin Context For The Linear Remodellingmentioning
confidence: 99%
See 3 more Smart Citations